Design of a CPW-Fed Band-Notched UWB Antenna Using a Feeder-Embedded Slotline Resonator - Amin M. Abbosh (International Journal of Antennas and Propagation)
A complete design method for a compact uniplanar ultra-wideband antenna with subband rejection capability is presented. A slotline resonator is incorporated in the coplanar waveguide feeder of the antenna to act as a bandstop filter, hence enabling the rejection of any undesired band within the passband of the antenna. Two samples of the proposed antenna were designed and manufactured. One of the developed antennas does not contain a resonator, whereas the other contains a slotline resonator. The designed antennas feature a compact size of 27 mm × 27 mm. Results of the simulation and measurement show that the designed antennas have a bandwidth from 3 GHz to more than 11 GHz. The results also reveal that the use of the resonator in the feeder of the antenna efficiently rejects any undesired subband, such as the 4.9–5.9 GHz band assigned for IEEE802.11a and HIPERLAN/2. The gain of the antennas with the resonator is about 2.2 dBi at the passband, while it is less than −8 dBi at the rejected subband.